1.(-2x^2)^3+(-4x^3)^2-(-2x)^2×(-1/2x)^4 2.(2×10^2)^3×(-3×10^6)^23.(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^20124.若m是正整数,求(-3)^m×(-1/3)^2m5.已知n为正整数,且(x^2)^n=9,求(-1/3x^3n)^2-3(
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 22:10:13
1.(-2x^2)^3+(-4x^3)^2-(-2x)^2×(-1/2x)^4 2.(2×10^2)^3×(-3×10^6)^23.(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^20124.若m是正整数,求(-3)^m×(-1/3)^2m5.已知n为正整数,且(x^2)^n=9,求(-1/3x^3n)^2-3(
1.(-2x^2)^3+(-4x^3)^2-(-2x)^2×(-1/2x)^4 2.(2×10^2)^3×(-3×10^6)^2
3.(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^2012
4.若m是正整数,求(-3)^m×(-1/3)^2m
5.已知n为正整数,且(x^2)^n=9,求(-1/3x^3n)^2-3(-x^2)^2n的值
6.已知x=2011,y=1/2011,求x^3×x^3m×(y^3)^m+1的值
1.(-2x^2)^3+(-4x^3)^2-(-2x)^2×(-1/2x)^4 2.(2×10^2)^3×(-3×10^6)^23.(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^20124.若m是正整数,求(-3)^m×(-1/3)^2m5.已知n为正整数,且(x^2)^n=9,求(-1/3x^3n)^2-3(
1、(-2x^2)^3+(-4x^3)^2-(-2x)^2×(-1/2x)^4=-8X^6+16X^6-1/4X^6=31/4X^6
2、(2×10^2)^3×(-3×10^6)^2=72×10^18
3、(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^2012=(1/2011×2011×1/2010×2010×1/2009×2009×……×1/3×3×1/2×2×1×1)^2012=1
4、1)当m是奇数时,(-3)^m×(-1/3)^2m=-(1/3)^m
2)当m是偶数时,(-3)^m×(-1/3)^2m=1/3^m
5、由已知求得x^2n=9,(-1/3x^3n)^2-3(-x^2)^2n=1/9X^6n-3X^4n=X^4n(X^2n/9-3)=-162
6、x^3×x^3m×(y^3)^m+1=2011^(3+3m)×1/2011^3(m+1)=1
3..(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^2012
=.(1/2011×2011×2010×1/2010×1/2009×2009×...×1/3×3×1/2×2×1×1)^2012
=1^2012
=1
4.(-3)^m×(-1/3)^2m
=(-3×-1/...
全部展开
3..(1/2011×1/2010×1/2009×...×1/3×1/2×1)^2012×(2011×2010×2009×...×3×2×1)^2012
=.(1/2011×2011×2010×1/2010×1/2009×2009×...×1/3×3×1/2×2×1×1)^2012
=1^2012
=1
4.(-3)^m×(-1/3)^2m
=(-3×-1/3)^m×(-1/3)^m
=1^m×(-1/3)^m
=(-1/3)^m
5.(-1/3x^3n)^2-3(-x^2)^2n=(-1/3x^2n)^3-3(-x^2n)^2=-27-243=-270
6.x^3×x^3m×(y^3)^m+1=x^3×(x×y)^3m+1=2011^3+1
收起
cxv